Second position without movement: Enclitic particles in Passamaquoddy - LeSourd, Philip S. (Proceedings of the 30th International Conference on Head-Driven Phrase Structure Grammar, 2023)
This paper presents an analysis of the second-position clitics of Maliseet-Passamaquoddy (Algonquian, New Brunswick and Maine) in the framework of Sign-Based Phrase Structure Grammar (Sag 2012). Unlike a previous transformational analysis (Johnson and Rosen 2015) that takes clitics to occupy a functional head in the left periphery, the proposal advanced here makes no use of movement or functional heads. Instead, clitic positions are determined by a small number of maximally simple constructional statements.